Agreement between test procedures for the single-leg hop for distance and the single-leg mini squat as measures of lower extremity function - Eva Ageberg; Anna Cronström (BMC, 2018)
Abstract Background Different test procedures are often used within performance-based measures, causing uncertainty as to whether results can be compared between studies. Thus, the aim of this study was to assess agreement between different test procedures for the single-leg hop for distance (SLHD) and the single-leg mini squat (SLMS), respectively, two commonly used tasks for assessing deficiency in lower extremity muscle function. Methods Twenty-three participants (20-42 years) with lower extremity injury performed the SLHD with arms free and with arms behind back, and the Limb Symmetry Index (LSI; injured leg divided by uninjured and multiplied by 100) was calculated. Another group of 28 participants (mean 18-38 years) performed five SLMSs at a pre-defined speed and maximum number of SLMSs during 30 seconds, and were visually observed and scored as either having a knee-over-foot or a knee-medial-to-foot position (KMFP). Results No systematic difference between test procedures for the LSI of the SLHD was noted (p=0.736), Cohen's kappa = 0.42. The Bland & Altman plot showed wide limits of agreement between test procedures, with particularly poor agreement for participants with abnormal LSI (<90%). Ten participants were scored as having a KMFP during five SLMSs at a predefined speed, while five had a KMFP during maximum number of SLMSs during 30 seconds (p=0.063, Cohen's kappa = 0.56). Conclusions The moderate agreement between the two test procedures for the SLHD and the SLMS, respectively, indicate that results from these different test procedures should not be compared across studies. SLHD with arms behind back, and five SLMSs at a pre-defined speed, respectively, were the most sensitive procedures to detect individuals with poor functional performance.